THE UNIVERSITY OF NARINO OBSERVATORY - Quijano Vodniza, Alberto; Rojas, Mario; Reyes, Karla; Perenguez, James; Mafla, Katherine (Revista de Ciencias, 2015)
Abstract The Astronomical Observatory of the University of Nari˜no was founded on March 2002 by Alberto Quijano Vodniza (Master’s Degree in Physics of the University of Puerto Rico). The Astronomical Observatory’s Director is a member of the AMERICAN ASTRONOMICAL SOCIETY – AAS since 2007. As a result of our research, we have published some books and we have participated on several international meetings. In the year 2008 our Observatory received the international code “H78” from the MINOR PLANET CENTER of USA , by providing this institution with high quality scientific data of asteroids as well as of comets. We presented in this work the last researches about asteroids and comets.